2009
DOI: 10.1111/j.1758-0854.2009.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal Detection Bias and Well‐Being in Close Relationships: Couples Experiencing Assisted Reproduction Treatment

Abstract: Communication between partners about each other's individual stress appraisals is considered to be pivotal for dyadic coping. So far, very little effort has been made to investigate the effects of accurate or biased detection of the partner's stress appraisals. On the basis of a dyadic stress model we predicted low appraisal detection bias among partners to be associated with better emotional well-being. Furthermore, we predicted appraisal detection bias to moderate the relationship between received support an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Third, the results of Experiment 2 suggest that our third hypothesis is supported as cloud‐based commensality can effectively enhance participants' perceived quality and strength of their romantic relationships. Given the ample opportunities for communication and interaction that videoconferencing tools provide (Pramudya et al, 2022; Spence et al, 2019), the effective interpersonal interaction generated during cloud‐based commensality is likely to promote the perception of close relationships among romantic couples as previous studies have indicated that high‐quality communication between couples can enhance their close relationships by promoting perceived support and synchronization (Kienle et al, 2009; Long et al, 2021). It should be noted that the influence of one‐time cloud‐based commensality on close relationships in this study may be limited to a short‐term effect, as the fundamental change in romantic relationships often relies on frequent communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the results of Experiment 2 suggest that our third hypothesis is supported as cloud‐based commensality can effectively enhance participants' perceived quality and strength of their romantic relationships. Given the ample opportunities for communication and interaction that videoconferencing tools provide (Pramudya et al, 2022; Spence et al, 2019), the effective interpersonal interaction generated during cloud‐based commensality is likely to promote the perception of close relationships among romantic couples as previous studies have indicated that high‐quality communication between couples can enhance their close relationships by promoting perceived support and synchronization (Kienle et al, 2009; Long et al, 2021). It should be noted that the influence of one‐time cloud‐based commensality on close relationships in this study may be limited to a short‐term effect, as the fundamental change in romantic relationships often relies on frequent communication.…”
Section: Discussionmentioning
confidence: 99%
“…Videoconferencing tools supporting cloud‐based commensality have been shown to offer ample opportunities for communication (Pramudya et al, 2022; Spence et al, 2019). Moreover, a high quality of communication between couples can promote their close relationship by fostering perceived support and synchronization (Kienle et al, 2009; Long et al, 2021). Therefore, it is plausible that cloud‐based commensality can also facilitate the development of close relationships between romantic couples (H3).…”
Section: Introductionmentioning
confidence: 99%
“…Despite having been initially developed and validated on an adult sample of cancer patients and their intimate partners (Schulz and Schwarzer, 2003), the BSSS has been successfully utilized to examine partner support in a variety of health-related contexts. Specifically, the BSSS has been utilized in research pertaining to Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS), fertility and perinatal research, health behaviour adherence, cancer research (Brondino et al, 2013; Gottlieb et al, 2014; Kienle et al, 2009; Luszczynska et al, 2005, 2007) and in psychological contexts such as stress and resilience (Testa et al, 2015). Not only have these scales been used in a variety of languages (including French; Acquadro et al, 2008) and contexts worldwide, research suggests that they have strong internal consistency (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Items are rated on a scale from 1 to 4, with a higher score indicating higher perceived social support. Originally designed for and validated in cancer surgery patients, the BSSS is used beyond this scope, including prenatal research (120,121). Eight items assess the amount of perceived emotional (e.g., "There is always someone there for me when I need comforting") and instrumental (e.g., "There are people who offer me help when I need it") social support.…”
Section: Perceived Social Supportmentioning
confidence: 99%